A Phase 1 Study of Prasugrel in Subjects with Sickle Cell Disease: Impact on Ex Vivo Platelet Reactivity - Jakubowski, Joseph A.; Zhou, Chunmei; Small, David S.; Winters, Kenneth J.; Lachno, D. Richard; Frelinger, Andrew L.; Howard, Jo; Jurcevic, Stipo; Payne, Christopher D. (Blood, 2011)
Abstract 1053 There is evidence of increased platelet reactivity in subjects with sickle cell disease (SCD). This could contribute to vaso-occlusive complications that characterize the disease; thus, antiplatelet therapy may be useful in the management of SCD. Prasugrel, a novel thienopyridine P2Y12 ADP receptor antagonist, is an effective inhibitor of ADP-mediated platelet activation and aggregation, but it has not been evaluated in SCD. The present study examined 1) the utility of various platelet assays used to assess platelet reactivity in blood from subjects with SCD; and 2) the impact of prasugrel on platelet reactivity in subjects with SCD compared to healthy controls. Twenty-six adult subjects were enrolled and 25 completed the study: 12 with SCD and 13 well-matched healthy controls. Subjects were examined before and after 12±2 days of treatment with oral prasugrel (5.0 mg/day for subjects weighing <60 kg and 7.5 mg/day for subjects weighing ≥60 kg). Platelet reactivity to ADP at baseline and after 12 days of prasugrel treatment was assessed by 1) maximum platelet aggregation (MPA) to 5mM ADP using light transmission aggregometry (LTA); 2) area under the aggregation curve (AU.min) to 6.5 mM ADP using impedance aggregometry (IA); 3) P2Y12 reactivity units (PRU) by VerifyNow P2Y12 (VN); and 4) platelet reactivity index (PRI) by vasodilator-stimulated phosphoprotein (VASP) phosphorylation. Baseline population differences and the within-group changes from baseline were analyzed using t-tests. The population differences for change from baseline were analyzed using an analysis of covariance model, with dose, subject group, and dose-by-subject group interaction as fixed effects, and baseline measurement as the covariate. All data are shown as mean±SD. At baseline and prior to initiation of prasugrel, subjects with SCD showed increased platelet reactivity vs. healthy controls, as evidenced by VN (PRU: 407.9±39.6 vs. 322.5±74.2, p=0.003) and IA (AU.min: 106.4±27.9 vs. 76.5±13.2, p=0.002). However, there was no difference between subjects with SCD and healthy controls in baseline platelet reactivity with LTA (MPA: 73.1±14.4% vs. 80.4±23.2%, p=0.376). Baseline PRI by VASP was significantly lower in subjects with SCD than in healthy controls (PRI: 59.4±23.3% vs. 78.9±10.0%, p=0.018) (Figure). After 12 days of treatment with prasugrel, all measures of platelet reactivity were significantly reduced compared with baseline in both SCD subjects and healthy controls (p< 0.05 for each assay); absolute change from baseline were as follows: LTA (−33.4 vs. −49.9), IA (−63.2 vs. −49.5), VN (−197.4 vs. −212.0), and VASP (−46.0 vs. −49.9; all SCD vs. control respectively, Figure). Changes from baseline in subjects with SCD compared to changes from baseline in healthy controls were not statistically significant after adjusting for baseline. Prasugrel was safe and well tolerated with no serious adverse events observed during the study. No subject discontinued the study due to an adverse event (AE) and the majority of AEs were mild. No subjects with SCD reported any bleeding-related AEs. At baseline, compared with healthy controls, subjects with SCD had increased platelet aggregation to ADP in whole blood by two independent assays (VN and IA), but similar aggregation in platelet-rich plasma (LTA). These results may be influenced by the lower hematocrit and higher platelet count in subjects with SCD. At baseline, subjects with SCD had more variable VASP PRI values resulting in reduced mean PRI. It remains to be determined whether this is a reflection of altered ADP and/or PGE1 signaling in certain individuals with SCD. Prasugrel administration significantly attenuated ADP-stimulated platelet reactivity in SCD subjects as measured by LTA, IA, VN, and VASP. The extent of prasugrel inhibition of platelet function in SCD was similar to that observed in prasugrel-treated healthy controls as measured by all 4 assays. The present results demonstrate that prasugrel inhibits platelet function in subjects with SCD, and that this inhibition can be monitored by a variety of assays. These results provide the basis for future studies evaluating prasugrel for the treatment of vascular complications associated with SCD. [Display omitted] p value: change from baseline; error bars: arithmetic mean±SD for combined dose data Jakubowski:Eli Lilly and Company: Employment, Equity Ownership. Off Label Use: This abstract discusses prasugrel treatment in patients with sickle cell disease. Please see USPI for most up-to-date information. Zhou:Eli Lilly and Company: Employment, Equity Ownership. Small:Eli Lilly and Company: Employment, Equity Ownership. Winters:Eli Lilly and Company: Employment, Equity Ownership. Lachno:Eli Lilly and Company: Employment, Equity Ownership. Frelinger:Takeda: Research Funding; GLSynthesis: Research Funding; Daiichi Sankyo Company, Ltd. and Eli Lilly and Company: Consultancy, Research Funding. Howard:Daiichi Sankyo Company, Ltd. and Eli Lilly and Company: Research Funding. Payne:Eli Lilly and Company: Employment, Equity Ownership.